Measuring value sensitivity in medicine. Issue 1 (December 2017) - Ineichen, Christian; Christen, Markus; Tanner, Carmen
Abstract Background Value sensitivity – the ability to recognize value-related issues when they arise in practice – is an indispensable competence for medical practitioners to enter decision-making processes related to ethical questions. However, the psychological competence of value sensitivity is seldom an explicit subject in the training of medical professionals. In this contribution, we outline the traditional concept of moral sensitivity in medicine and its revised form conceptualized as value sensitivity and we propose an instrument that measures value sensitivity. Methods We developed an instrument for assessing the sensitivity for three value groups (moral-related values, values related to the principles of biomedical ethics, strategy-related values) in a four step procedure: 1) value identification (n = 317); 2) value representation (n = 317); 3) vignette construction and quality evaluation (n = 37); and 4) instrument validation by comparing nursing professionals with hospital managers (n = 48). Results We find that nursing professionals recognize and ascribe importance to principle-related issues more than professionals from hospital management. The latter are more likely to recognize and ascribe importance to strategy-related issues. Conclusions These hypothesis-driven results demonstrate the discriminatory power of our newly developed instrument, which makes it useful not only for health care professionals in practice but for students and people working in the clinical context as well.